VIRUS DESTROYER GAME FOR EDUKATING HEALTH PROTOCOL AND LEARNING MEDIA OF VIRUS DURING COVID-19 PANDEMIC - Lilik Lilik Muntamah (Balai Diklat Keagamaan Denpasar, 2022)
At the end of 2019, the world was shocked by the spread of the Corona Virus that causes Corona Virus Disease (COVID-19). The Covid-19 pandemic has changed all aspects of life, one of which is the world of education. The government's stay at home policy changes learning to online-based distance learning. So that students cannot be separated from the use of smartphones. Therefore, learning media is needed for education on health protocols and interesting virus-based material on smartphones. The purpose of this study is to provide media that interesting to the public for the prevention of COVID-19 and to provide learning media about Viruses in Biology subjects. This research is developmental research, with research stages covering game development, game algorithms, and game testing. The data were analyzed descriptively quantitatively using the Guttman Scale and Likert Scale. The results showed that the Virus Destroyer Game received a positive response from respondents with a percentage of 83.9% and included a very feasible virus learning media according to the validation results with a percentage of 90.83%. The conclusion of this research is that, the Virus Destroyer Game which was developed, received a positive response as an educational media for preventing COVID-19 and also feasible to be a viral KD learning media. The implication of this research is that students better understand the importance of implementing health protocols to break the spread of Covid-19 in a fun way. Keywords: game education, health protocol, Virus Destroyer Game